The Shades of Emptiness: The Subjective Model of Genuineness in the Teachings of Wei Yao - Mozias, Ilia (Journal of Chinese religions, 2025)
This paper examines the model of genuineness proposed by Wei Yao 魏堯 (fl. 1920-1926), a master of the Western School of internal alchemy. Wei diverges from the dominant and conventional forms of alchemical practice, emphasizing transcendence through emptiness while downplaying the traditional focus on the body as a central medium of transformation. He identifies two selves: the "genuine self," rooted in emptiness, and the "false self," which takes control after birth, scattering emptiness throughout the body, mind, and space. Wei's method centers on external breathing, allowing practitioners to gather fragmented emptiness and form intention (yi 意) - the manifestation of the genuine self and seed of an immortal body. Through cycles of forgetfulness and concentration, practitioners refine this intention, coalescing the spirit into new flesh. This process culminates in the visualization of golden light, representing the birth of the immortal body. Wei's model portrays genuineness as subjective, emerging from the practitioner's ability to control imagination and manipulate the shades of emptiness.